Analisis Interaksi Obat Potensial pada Resep Pasien Geriatri di Instalasi Farmasi Rumah Sakit Umum Daerah - Mukriani, Mukriani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Background: Geriatric patients are a vulnerable group to drug side effects due to decreased physiological function and the presence of multiple chronic diseases that require polypharmacy therapy. The combination of various drugs in one prescription increases the possibility of potential drug-drug interactions (pDDIs) which can have a negative impact on patient safety. Objective: This study aims to analyze the frequency, type, and severity of potential drug interactions found in geriatric patient prescriptions at the pharmacy installation of the Regional General Hospital (RSUD), and to identify the drugs that most often cause interactions. Methods: This study used a retrospective descriptive design with a quantitative approach. Data were collected from 250 copies of prescriptions for patients aged ≥60 years who received outpatient and inpatient care during January–March 2025. Interaction analysis was performed using the Medscape Drug Interaction Checker, and the results were classified based on severity (minor, moderate, major). Results: From a total of 250 prescriptions analyzed, 418 potential drug interactions were found, consisting of 38.5% major interactions, 50.2% moderate interactions, and 11.3% minor interactions. The drugs most frequently involved in interactions included amlodipine, simvastatin, furosemide, aspirin, and metformin. Conclusion: The results of the study indicate that the incidence of potential drug interactions in geriatric patients is relatively high. This indicates the need for a more careful prescription monitoring system, active involvement of clinical pharmacists, and the application of system-based technology to detect and manage drug interactions effectively. This step is important to improve patient safety and the effectiveness of therapy among the elderly.